UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL KOOPERATIF TIPE STAD PADA SISWA KELAS IV SD NEGERI 14 BATU BASA KECAMATAN PARIANGAN - Nadra Nadra (JURNAL MANAJEMEN PENDIDIKAN, 2020)
To create a learning process that is fun, exciting and can improve learning outcomes, it is necessary to have an interesting learning change that is applying STAD cooperative learning models and quizzes. The results of the study in the first cycle, classical learning activities only reached 52.94%. This has not yet reached the expected learning process improvement of yaitu 75%. But in the learning process the group has reached 88% with a target of ? 75%. While learning outcomes only reached 66.47% while the target determined 100% completely reached nilai 75%. To improve the classical learning process in the second cycle each student is given a visual aid a number of flat shapes to be formed into a variety of combinations to make questions. In Cycle II there was an increase in the classical learning process to 65.88% because there were 3 students asking questions and 14 students taking notes, where in Cycle I there were no students asking and taking notes. The group learning process increased to 91.05%. While learning outcomes reached an average of 76.47%. In Cycle III, in addition to the display for each student, to be able to find the formula for building area based on the area of flat shape that has been mastered by students, it is also added by giving homework assignments in the form of exercises. This is due to the increasingly difficult competency to master. In cycle III an increase in classical learning process was quite high to 84.61%. This is due to the increasing number of students who ask questions as many as 10 students and record as many as 4 students. The group learning process increased to 97.61%. While the learning outcomes reached an average of 79.61% with 100% of students achieving a value of ? 75. Thus all the targets set had been achieved. Based on the results of the study it can be concluded that the STAD type cooperative learning model can encourage students to learn about the area of more enthusiasm, improve the learning process, and learning outcomes.